Behavioral Activation and Problem-Solving Therapy for Depressed Breast Cancer Patients: Preliminary Support for Decreased Suicidal Ideation. (November 2013) - Hopko, D. R.; Funderburk, J. S.; Shorey, R. C.; McIndoo, C. C.; Ryba, M. M.; File, A. A.; Benson, K.; Vitulano, M.
Major depressive disorder (MDD) is the most common psychiatric disorder in breast cancer patients. The prevalence of suicidal ideation in breast cancer patients is considerable, and relative to the general population, the prevalence of completed suicide is elevated, particularly in cancer patients with MDD. A major component of suicide prevention is effective treatment of MDD. Although some research has explored the utility of psychotherapy with breast cancer patients, only three trials have explored the benefits of behavior therapy in patients with well-diagnosed MDD and there has been no systematic investigation of the potential benefits of psychotherapy toward reducing suicidal ideation in breast cancer patients. As a follow-up to a recently completed randomized trial, this study examined the efficacy of 8 weeks of behavioral activation treatment for depression (BATD) and problem-solving therapy (PST) in reducing depression and suicidal ideation, as well as increasing hopefulness in breast cancer patients with MDD ( n = 80). Across both treatments, GEE analyses revealed decreased depression and suicidal ideation and increased hopefulness at posttreatment, results that were maintained at 12-month follow-up. Moreover, follow-up patient contact at approximately 2 years posttreatment yielded no indication of completed suicide. Although these data are preliminary, BATD and PST may represent practical approaches to decrease suicidal ideation in depressed breast cancer patients.